2023
DOI: 10.3390/electronics12194026
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Grey Wolf Optimization Algorithm for Mobile Robot Path Planning

Lili Liu,
Longhai Li,
Heng Nian
et al.

Abstract: In this study, an enhanced hybrid Grey Wolf Optimization algorithm (HI-GWO) is proposed to address the challenges encountered in traditional swarm intelligence algorithms for mobile robot path planning. These challenges include low convergence accuracy, slow iteration speed, and vulnerability to local optima. The HI-GWO algorithm introduces several key improvements to overcome these limitations and enhance performance. To enhance the population diversity and improve the initialization process, Gauss chaotic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…The mathematical model of this problem is expressed as follows. Min f (x) = 0.6224x 1 x 3 x 4 + 1.7781x 2 x 2 3 + 3.1661x 2 1 x 4 + 19.81x 2 1 x 3 (16) x = (x 1 , x 2 , x 3 , x 4 ) = (T s , T h , R, L) Equation ( 16) constitutes the objective function of the classical pressure vessel design problem, delineating the minimization objective. This objective pertains to the discovery of an optimal configuration for the four design variables, namely, shell thickness Ts, head thickness Th, inner radius R, and cylinder length L. In the literature, this problem is solved by using the mathematical methods of an augmented Lagrangian multiplier [55] and branch-and-bound [56] classical techniques.…”
Section: Solving a Pressure Vessel Design Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The mathematical model of this problem is expressed as follows. Min f (x) = 0.6224x 1 x 3 x 4 + 1.7781x 2 x 2 3 + 3.1661x 2 1 x 4 + 19.81x 2 1 x 3 (16) x = (x 1 , x 2 , x 3 , x 4 ) = (T s , T h , R, L) Equation ( 16) constitutes the objective function of the classical pressure vessel design problem, delineating the minimization objective. This objective pertains to the discovery of an optimal configuration for the four design variables, namely, shell thickness Ts, head thickness Th, inner radius R, and cylinder length L. In the literature, this problem is solved by using the mathematical methods of an augmented Lagrangian multiplier [55] and branch-and-bound [56] classical techniques.…”
Section: Solving a Pressure Vessel Design Problemmentioning
confidence: 99%
“…Furthermore, Hu et al [14] and Boursianis et al [15] both demonstrated GWO's utility in the prediction of wind speed and the optimization of antenna design and synthesis, respectively. Liu et al [16] incorporated the Gray Wolf Optimizer (GWO) algorithm into the domain of robotic path planning. Through the integration of a suite of enhancement techniques, this approach facilitated notable advancements in the practical application of path planning, thereby offering a more efficacious optimization strategy that contributes significantly to the progression of research in robotic path planning.…”
Section: Introductionmentioning
confidence: 99%